The hydraulic fracturing design technology and application of geological-engineering integration for tight gas in jinqiu gas field - Zeng, Ji; Li, Wenzhe; Fang, Hongming; Huang, Xin; Wang, Tao; Zhang, Dandan; Yuan, Shuhang (Frontiers in Energy Research, 2022)
Tight sandstone gas reservoir of Shaximiao formation in Jinqiu Gas field has the advantages of wide distribution and abundant resources. Due to its low porosity, low permeability and strong spatial heterogeneity, this reservoir puts forward high requirements for sweet spot identification, cluster design and hydraulic fracture morphology prediction. Previous stimulation technology can not meet the technical-economical indication. This paper summarizes previous stimulation experience, established a geological-engineering integration model. This model layout the relationship among engineering characteristics, hydraulic fracture shape and well productivity. Then, the key controlling factors are identified for further optimization. And differentiation stimulation strategies are carried out based on different reservoir quality and different channel sand. Field tests show the average test production in the target field increased from 50,500 to 434,300 cubic meter per day laying a solid foundation for the efficient development of tight gas in central Sichuan.